Legal Provisions Of Polygamy In Bangladesh: A Comparison Between Muslim Family Law Ordinance 1961 And Islamic Jurisprudence - Muhammad Rafiqul Hoque; Muhammad Mustaqim bin Mohd Zarif (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI007 65-76